Pengaruh Modal Psikologis dan Komitmen Organisasi terhadap Kohesivitas Kelompok Pengurus Himpunan Mahasiswa Jurusan Fakultas Ushuluddin dan Humaniora Universitas Islam Negeri Antasari Banjarmasin - Dharmawan, Muhammad Rizky; Faridah, Siti; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2021)
Group cohesiveness is a state or condition in which group members have an interest each other. This will make group cooperation and unity owned will increase work spirit to make a good performance. Group cohesiveness is unity in the group, each member enjoys interaction with each other, and has a certain time together and there is high work spirit in it. Each group has a different level of cohesiveness which causes its members to be attracted to each other and motivated to stay in the group, and a cohesive group will be more productive than a less cohesive group. Therefore, the researcher interested in conducting research on the Effect of Psychological Capital and Organizational Commitment on the Group Cohesiveness of the Majoring Student Associationof the Faculty of Ushuluddin and Humanities State Islamic University of Antasari BanjarmasinThis research uses a correlational method with a quantitative approach. The population in this study were the administrators of 4 Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin, which is Islamic Psychology, Aqidah and Islamic Philosophy, Al-Qur'an Science and Tafsir, and Religions Studies, amounting to 198 people, then using a saturated sampling technique or total sampling that is using all members of the population as a sample. Based on this research, the results obtained: 1) There is a significant influence between psychological capital on the group cohesiveness of Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin with a significance of 0,000 (p <0,05) and an effective contribution of 36,2%. 2) There is a significant influence between organizational commitment on the group cohesiveness of Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin with a significance of 0,000 (p <0,05) and an effective contribution of 47,8%. 3) There is a significant influence between psychological capital and organizational commitment on the group cohesiveness of Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin with a significance of 0,000 (p <0,05) and an effective contribution of 57,8%. 4) The results of psychological capital data for Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin in the low category were 12,6% (25 people), the medium category was 77,8% (154 people), and the high category was 9,6% (19 people). 5) The results of organizational commitment data for Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin in the low category were 10,1% (20 people), the medium category was 75,8% (150 people), and the high category was 14,1% (28 people). 6) The results of group cohesiveness data for Majoring Student Associations from the Faculty of Ushuluddin and Humanities State Islamic University of Antasari Banjarmasin in the low category were 11,6% (23 people), the medium category was 74,7% (148 people), and the high category was 13,6% (27 people).